Two-Phase Pressure Drop Calculations in Small Diameter Inclined Tubes - Autee, Arun; Rao, S.Srinivasa; Puli, Ravikumar; Shrivastava, Ramakant (International Journal of Engineering and Technology, 2012)
Effect of inclination on two-phase frictional pressure drop was investigated in small diameter circular tubes with inner diameters of 4.0, 6.0, 8.0 and 10.0 mm using air and water. Pressure drop was measured and compared with various existing models commonly used for macro and micro channels such as homogeneous, Lockhart-Martinelli, Chisholm, Friedel, Mishma Hibiki, and Zang Mishma. It was found that existing correlations are inadequate in predicting pressure drop for small diameter inclined tubes. The void fraction is calculated using a general void fraction correlation in two-phase flow for various pipe orientations. Based on analysis of present experimental frictional pressure drop data, a correlation is proposed for predicting Chisholm parameter “C” in small diameter inclined tubes. There was a significant ordering of pressure drop data with respect to Reynolds number, Webber number and Bond number for each diameter.